Primary School Teacher Performance in Creating Quality Learning - Zulkarnain, Razef; Nellitawati, Nellitawati; Hadiyanto, Hadiyanto; Alkadri, Hanif; Widiawati, Widiawati (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to determine the performance of the primary school teachers in realizing quality learning. The research method used was a quantitative method with correlational descriptive techniques. The research was carried out in the state primary schools in the Kamang Baru district with the research sample of 105 respondents. Research data were collected by using a Likert scale questionnaire consisting of the five alternative answers. The data analysis technique used was descriptive analysis by finding the average score, calculating percentages, and setting achievement criteria. Results showed that the teacher’s performance was in a good category. It means that teachers have performed well in realizing quality learning. The results imply the need for continuous improvement and development of teacher performance.